Female congenital aphallia: a unique case of congenital absence of the clitoris with an ectopic labium majorum. Issue 1 (January 2021) - Almutadares, Mahmoud; Evans, Jane; Sellers, Elizabeth; Morris, Amanda; Zapata-Aldana, Eugenio
Abstract : The spectrum of disorders of sexual development includes anatomical abnormalities of the external genitalia, the phenotypic variability of which and the underlying causes are numerous. However, female aphallia and ectopia of the labium majorum appear to be some of the rarest forms of external genitalia malformations. Aphallia is mostly described in males with a frequency of less than one per 40 000 male newborns. Although syndromic forms of aphallia in females have been reported, for example, in Robinow, CHARGE, and Prader–Willi syndrome, reports of isolated female aphallia are meager. Here, we describe the first case of isolated agenesis of the clitoris with an ectopic labium majorum and review the literature of this uncommon malformation and its potential dysmorphogenetic mechanism. We emphasize the need for a routine exhaustive physical examination to identify and characterize this unusual malformation correctly so that families can be appropriately counseled as to cause and potential complications.